Effects of lecithin: Cholesterol acyltransferase genotypes, enzyme levels, and activity on high-density lipoprotein levels - EREN, FATİH (ELSEVIER SCIENCE INC, 2011)
BACKGROUND: Lecithin:cholesterol acyltransferase (LCAT) is one of the key enzymes controlling cholesterol homeostasis and plays a primary role in high-density lipoprotein cholesterol (HDL-C) maturation. OBJECTIVE: The aim of our study was to evaluate the effects of LCAT gene polymorphisms 511C/T (exon4), 4886C/T (rs5923), and 608C/T (rs5922) on LCAT enzyme level, activity, and HDL-C levels. METHODS: The study population was selected from consecutive subjects with low (<35 mg/dL) and high HDL-C levels (>65 mg/dL) seen in our lipid clinic. LCAT polymorphisms were analyzed with a restriction fragment length polymorphism assay. LCAT activity and levels were measured by colorimetric enzymatic and enzyme-linked immunoassay methods, respectively. RESULTS: The 4886C/T polymorphism was the most commonly observed variant of LCAT gene. T-allele frequencies in subjects with low (n = 50) and high (n = 50) HDL-C were 0.54 and 0.37, respectively (P = .019). genotype was more common among low HDL-C group (30% vs 14%, P = .05). The effects of LCAT enzyme appeared to depend on the HDL-C level. In subjects with low HDL-C, LCAT enzyme levels correlated positively with body mass index (P < .001, r = 0.544), HDL-C (P = .006, r = 0.404), triglycerides (P = .001, r = 0.487), total cholesterol (P < .001, r = 0.541), and low-density lipoprotein-cholesterol (P = .001, r = 0.477) levels. LCAT activity correlated positively with fasting glucose levels (P = .008, r = 0.390). CONCLUSION: LCAT genotype, enzyme level, and activity modulate HDL-C metabolism, particularly among subjects with low HDL-C levels. (C) 2011 National Lipid Association. All rights reserved.
Keywords: Coronary artery disease; Enzyme activity; Enzyme level; Genetic polymorphisms; High-density lipoprotein-cholesterol; Lecithin:cholesterol acyltransferase; CORONARY-ARTERY-DISEASE; HEART-DISEASE; MYOCARDIAL-INFARCTION; TURKISH POPULATION; HDL3 SUBFRACTIONS; RISK; GENE; ATHEROSCLEROSIS; POLYMORPHISMS; LCAT